The good news is the bad news is wrong - Wattenberg, Ben J. (New York : Simon and Schuster, 1984)
This text gives a broad-scale, easily-understandable, demographic portrait of the USA with hard data from the US census and many other sources. Featured topics include: economic policy; political and social processes; energy; education; fiscal policies; religion; philosophy; and public policy.
Includes index.
rpm 30/05/2017
Loans
Keywords: Quality of life; Quality of life -- United States; Social indicators; Social condition; Cost and standard of living; United States -- Social conditions -- 1980.; United States